Deinococcus radiodurans Exopolysaccharide Inhibits Staphylococcus aureus Biofilm Formation - Chen, Fengjia; Zhang, Jing; Ji, Hyun Jung; Kim, Min-Kyu; Kim, Kyoung Whun; Choi, Jong-Il; Han, Seung Hyun; Lim, Sangyong; Seo, Ho Seong; Ahn, Ki Bum (Frontiers in Microbiology, 2021)
Deinococcus radiodurans is an extremely resistant bacterium against extracellular stress owing to on its unique physiological functions and the structure of its cellular constituents. Interestingly, it has been reported that the pattern of alteration in Deinococcus proportion on the skin is negatively correlated with skin inflammatory diseases, whereas the proportion of Staphylococcus aureus was increased in patients with chronic skin inflammatory diseases. However, the biological mechanisms of deinococcal interactions with other skin commensal bacteria have not been studied. In this study, we hypothesized that deinococcal cellular constituents play a pivotal role in preventing S. aureus colonization by inhibiting biofilm formation. To prove this, we first isolated cellular constituents, such as exopolysaccharide (DeinoPol), cell wall (DeinoWall), and cell membrane (DeinoMem), from D. radiodurans and investigated their inhibitory effects on S. aureus colonization and biofilm formation in vitro and in vivo. Among them, only DeinoPol exhibited an anti-biofilm effect without affecting bacterial growth and inhibiting staphylococcal colonization and inflammation in a mouse skin infection model. Moreover, the inhibitory effect was impaired in the ∆dra0033 strain, a mutant that cannot produce DeinoPol. Remarkably, DeinoPol not only interfered with S. aureus biofilm formation at early and late stages but also disrupted a preexisting biofilm by inhibiting the production of poly-N-acetylglucosamine (PNAG), a key molecule required for S. aureus biofilm formation. Taken together, the present study suggests that DeinoPol is a key molecule in the negative regulation of S. aureus biofilm formation by D. radiodurans. Therefore, DeinoPol could be applied to prevent and/or treat infections or inflammatory diseases associated with S. aureus biofilms.